COVID-19 pandemic, domestic violence, and victims’ access to services: findings from a survey of victim service providers in the US - Yasemin Irvin-Erickson; Mangai Natarajan; Lindsay Smith; Brittany Suh (Crime Science)
Abstract Background This study aims to explore the relationship between the COVID-19 pandemic and domestic violence victims’ help-seeking from victim service providers in the United States using the framework of Routine Activities Theory. Methods The analysis is based on primary data collected from an online survey that represents a national sample of organizations serving domestic violence victims across the states and territories of the United States. We examined the change in the number of domestic violence clients and the severity of domestic violence cases that came to the attention of these organizations in the first year of the pandemic. Results Our regression analysis suggests a significant decrease in the number of new domestic violence clients coming to the attention of organizations primarily serving victims in rural areas and organizations partially operating during the pandemic lockdown; a decline in the number of returning domestic violence clients among organizations with a 24-hour hotline; and an increase in the number of returning clients among organizations that engaged in targeted community outreach during the initial lockdown. We further found that organizations that have targeted programs for Black/African American and Hispanic domestic violence victims were more likely to report an increase in the severity of abuse that came to their attention during the first year of the pandemic. Conclusions Crime opportunity theories, such as the Routine Activities Theory, can be extremely beneficial in understanding the criminogenic environment for domestic violence and other crimes during the COVID-19 pandemic. Addressing and responding to a public health emergency at the scale of the COVID-19 pandemic that can heighten the risk of domestic violence due to various stressors and physical and social isolation requires a holistic approach to emergency preparedness. Planning should address the risk of domestic violence, the barriers to help-seeking, and identify communities and the victim groups that are particularly vulnerable to victimization and aggravated outcomes following such experiences.